An Historical Perspective on Efforts to Treat Transmissible Spongiform Encephalopathy - Brown, P. (CNS & Neurological Disorders - Drug Targets, 2009)
Efforts to treat transmissible spongiform encephalopathy (TSE) date back to the middle of the 20th century. Early studies were colored by the belief that TSE was caused by a ‘slow’ or ‘unconventional’ virus, and a variety of antiinfective agents, together with scores of drugs drawn at random from other categories, predictably failed to provide any benefit, apart from polyanionic compounds and polyene antibiotics that prolonged the incubation period of disease in experimental animals. With the discovery in the 1980's that TSE apparently results from the malformation of a normal host protein, attempts at treatment could at last be rationally focused, and can be broadly categorized as genetic, immunologic, and pharmacologic. Genetic ‘neutralization’ of the pathogen has shown excellent results in experimental animals but is unlikely to be useful until the same kind of engineering can be effectively applied to humans. Immunologic methods to accomplish the same result have also shown some success in animals, but forays into the pharmacologic realm have been generally disappointing. Most reported ‘successes’ have been limited to prolonged incubation periods, and even then only when the treatment was begun at or near the time of infection, which is not known in sporadic or familial human disease. However, a few methods using the more rigorous model of treatment nearer the onset of symptomatic disease have begun to yield promising results that, if coupled with a practical screening test for pre-clinical infection, would be the optimal strategy for prevention or cure.